Probiotic characterization and antioxidant properties of Weissella confusa KR780676, isolated from an Indian fermented food. (November 2018) - Sharma, Shivangi; Kandasamy, Sujatha; Kavitake, Digambar; Shetty, Prathapkumar Halady
Abstract: Weissella confusa (KR780676), isolated from an Indian traditional fermented food (Idli batter) exhibited good growth and survival under simulated gastro-intestinal conditions. Cells also showed strong cell surface hydrophobicity, auto-aggregation and moderate biofilm formation ability indicating the potential for adhesion on to the host cell as multiple aggregates. Thermostability, cholesterol removal, β-galactosidase production and proteolytic activity of the strain indicated potential functional ability. Cell-free extract showed prominent hydroxyl radical scavenging activity, while intact cells exhibited significant DPPH, superoxide anion radical scavenging potential and lipid peroxidation inhibition. CLSM imaging confirmed inhibition of biofilm formation by P. aeruginosa KT266804. Besides, probiotic and functional properties, safety evaluation results revealed no haemolytic, DNase and gelatinase activity. Further, sensitivity towards antibiotics confirmed the potential of W. confusa as a functional starter culture candidate in fermented foods. Highlights: W. confusa demonstrated remarkable acid, bile, transit, lysozyme and heat tolerance. Aggregation, hydrophobicity and biofilm formation showed potential adhesion in gastro intestinal tract. Cholesterol removal, β-galactosidase and antioxidant activity prove health benefits. Safety evaluation confirmed no haemolytic, DNase and gelatinase activity.